DAMPAK RENDAHNYA PENDAPATAN ASLI DAERAH TERHADAP LEMAHNYA STANDART OPERATING PROCEDURES PADA UPTD UJI KIR DINAS PERHUBUNGAN BOJONEGORO - Hasan Bisri (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2012)
This research aims to increase awareness of civil servants to always provide excellent service to the community and between intansi especially in Bojonegoro. methods used in this study using a qualitative approach, which is intended to understand the interaction of actors and community service served. This interaction affects the quality of service from different points of view. Therefore, this study also aimed to analyze and understand why they are doing social action; choose based interaction options for economical manner. Here we also see the reason or rationality underlying the formation of interactions in the process of public services.